Gastrointestinal Symptoms in Children with Autism Spectrum Disorder: Clinical Characteristics, Contributing Factors and Management Strategies - Zhang, Yichun; Song, Hujie (Journal of Contemporary Medical Practice, 2026)
Gastrointestinal (GI) symptoms are common comorbid conditions in children with autism spectrum disorder (ASD), including constipation, abdominal pain, diarrhea, abdominal distension, and gastroesophageal reflux. These symptoms may affect dietary intake, nutritional status, growth, sleep, and quality of life. Due to limited communication abilities, some children with ASD may have difficulty expressing gastrointestinal discomfort and may instead present with food refusal, crying, sleep disturbance, or behavioral changes, increasing challenges in clinical recognition. The development of GI symptoms in children with ASD is likely associated with multiple factors, including food selectivity, dietary patterns, bowel habits, sensory characteristics, psychological stress, medication use, and alterations in gut microbiota. However, current evidence is mainly derived from observational studies, and causal relationships remain unclear. Microbiome studies are also influenced by confounding factors such as diet, age, constipation, and medication exposure, and no validated biomarkers are currently available for clinical diagnosis or treatment monitoring. Clinical assessment should follow general pediatric gastrointestinal principles, including detailed history taking, physical examination, and identification of alarm features, while incorporating ASD-related characteristics such as communication abilities, sensory responses, feeding behaviors, and toileting patterns. Management should focus on specific gastrointestinal disorders and include appropriate nutritional and behavioral interventions when indicated. Evidence supporting probiotics, prebiotics, restrictive diets, and fecal microbiota transplantation remains limited, and these approaches should not replace standard clinical evaluation and treatment. This review summarizes the clinical characteristics, contributing factors, assessment approaches, and management strategies of GI symptoms in children with ASD, providing a reference for clinical recognition and individualized management.